A molecular Fe-complex as a catalyst probe for in-gel visual detection of proteins via signal amplification. Issue 83 (15th July 2015) - Kumari, Sushma; Panda, Chakadola; Mazumdar, Shyamalava; Sen Gupta, Sayam
Abstract : We report the use of a molecular peroxidase mimic biuret FeTAML for chemoselective labeling of proteins and the subsequent visual detection (<0.1 pmoles) of the conjugate in a polyacrylamide gel by catalytic signal amplification. Abstract : We report the use of a molecular peroxidase mimic biuret-Fe-TAML for chemoselective labeling of proteins and the subsequent visual detection (<0.1 pmoles) of the conjugate in a polyacrylamide gel by catalytic signal amplification. Use of this probe in activity based protein profiling (ABPP) of serine proteases is also demonstrated.